Wntless regulates lipogenic gene expression in adipocytes and protects against diet-induced metabolic dysfunction - Devika P. Bagchi; Ziru Li; Callie A. Corsa; Julie Hardij; Hiroyuki Mori; Brian S. Learman; Kenneth T. Lewis; Rebecca L. Schill; Steven M. Romanelli; Ormond A. MacDougald (Elsevier, 2020)
Objective: Obesity is a key risk factor for many secondary chronic illnesses, including type 2 diabetes and cardiovascular disease. Canonical Wnt/β-catenin signaling is established as an important endogenous inhibitor of adipogenesis. This pathway is operative in mature adipocytes; however, its roles in this context remain unclear due to complexities of Wnt signaling and differences in experimental models. In this study, we used novel cultured cell and mouse models to investigate functional roles of Wnts secreted from adipocytes. Methods: We generated adipocyte-specific Wntless (Wls) knockout mice and cultured cell models to investigate molecular and metabolic consequences of disrupting Wnt secretion from mature adipocytes. To characterize Wls-deficient cultured adipocytes, we evaluated the expression of Wnt target and lipogenic genes and the downstream functional effects on carbohydrate and lipid metabolism. We also investigated the impact of adipocyte-specific Wls deletion on adipose tissues and global glucose metabolism in mice fed normal chow or high-fat diets. Results: Many aspects of the Wnt signaling apparatus are expressed and operative in mature adipocytes, including the Wnt chaperone Wntless. Deletion of Wntless in cultured adipocytes results in the inhibition of de novo lipogenesis and lipid monounsaturation, likely through repression of Srebf1 (SREBP1c) and Mlxipl (ChREBP) and impaired cleavage of immature SREBP1c into its active form. Adipocyte-specific Wls knockout mice (Wls-/-) have lipogenic gene expression in adipose tissues and isolated adipocytes similar to that of controls when fed a normal chow diet. However, closer investigation reveals that a subset of Wnts and downstream signaling targets are upregulated within stromal-vascular cells of Wls-/- mice, suggesting that adipose tissues defend loss of Wnt secretion from adipocytes. Interestingly, this compensation is lost with long-term high-fat diet challenges. Thus, after six months of a high-fat diet, Wls-/- mice are characterized by decreased adipocyte lipogenic gene expression, reduced visceral adiposity, and improved glucose homeostasis. Conclusions: Taken together, these studies demonstrate that adipocyte-derived Wnts regulate de novo lipogenesis and lipid desaturation and coordinate the expression of lipogenic genes in adipose tissues. In addition, we report that Wnt signaling within adipose tissues is defended, such that a loss of Wnt secretion from adipocytes is sensed and compensated for by neighboring stromal-vascular cells. With chronic overnutrition, this compensatory mechanism is lost, revealing that Wls-/- mice are resistant to diet-induced obesity, adipocyte hypertrophy, and metabolic dysfunction.